The polyamine transport system: A means of selective delivery of potentially toxic agents to cancer cells? - Abdul Ghani, Radiah; Palmer, Andrew J.; Kaur, Navneet; Phanstiel, Otto; Wallace, Heather M. (ELSEVIER, 2009)
The development of a means of delivering drugs selectively to cancer cells is a huge challenge in cancer research today. The development of such methods would decrease the non-specific toxicities which limit the use of most anti-cancer drugs. One way to achieve this is to utilise a specific transport mechanism such as polyamine transport system (PTS). Polyamine transport system is an energy-dependent process that is upregulated in cancer cells which have a high requirement for polyamines (Gardner et al., 2004). Exogenous polyamines are taken up into the cells via PTS. In addition, there have been a number of studies indicating that the PTS is not restricted to natural polyamines but can accommodate a wide range of substrates (Phanstiel et al., 2004). With this knowledge, a strategy was devised to use the polyamines as a means of vectoral transport into cells to introduce potentially toxic agents which would not normally enter cancer cells. The aim is to increase the selectivity of anti-cancer agents and minimise the side effects in normal cells (Phanstiel et al., 2004). To this end, a series of compounds combining the DNA intercalator, anthracene, with a polyamine side chain were synthesized (Phanstiel et al., 2000).